Pemodelan Sorpsi Isotermi dan Pendugaan Umur Simpan Beras Pratanak pada Kemasan Plastik Film - Hasniar .; Rokhani Hasbullah; I Wayan Astika (Jurnal Keteknikan Pertanian, 2019)
AbstractMoisture sorption isotherms have an important role in the quantitative approach to predict shelf life of the food due to their sensitivity to moisture changes. The objectives of this research were to determine the equilibrium moisturecontent ofparboiled rice,to findthe bestmodel todescribe thesorption isotherm curve ofparboiled rice, and to predict shelf-life of the parboiled rice during storage. Moisture sorption isotherms of parboiled rice were determined using the standard gravimetric static methodat temperature of 30o, which involves the use saturated salt solution to maintain a fixed equilibrium relative humidity. To achieve different relative humidity environments, aqueous solutions of NaOH, MgCl2, Mg(NO3)2, KI, NaCl, KCl, Na2SO4, and NH4H2PO4 to have relative humidity of 7%, 33%, 52%, 69%, 75%, 84%, 87% dan 92%. Five gram samples of parboiled rice were stored in dessicators. The samples were weighed periodically until they constant. The Hasley, Oswin, Henderson, Chen-Clayton and Caurie models were applied to describe the relationship between equilibrium moisture content and relative humidity. The mean relative deviation was used to evaluate the goodness of each models. The result showed that equilibrium moisture content of parboiled rice fromrelative humidity of 7%, 33%,52%,69%, 75%, 84%, 87% dan 92% respective of 6.93% dry basis (db), 11.09%db, 14.22% db, 15.86% db, 17.05% db, 19.68% db, 23.92% db, dan 25.59% db. Water sorption isotherm parboiled rice had sigmoid shape. The Oswin model was found to be the best model to describe the experimental sorption data for parboiled rice was the value MRD is 3.85 and R2 is 0.98. Parboiled rice packaged with HDPE, LDPE, and PP have a predict shelf-life respective of 2.2, 2.3 and 8.8 year.AbstrakSorpsi isotermi memiliki peran penting dalam pendekatan kuantitatif untuk menduga umur simpan bahan yang rentan terhadap perubahan kelembaban. Tujuan dari penelitian ini adalah untuk menentukan kadar air kesetimbangan beras pratanak, menentukan model yang tepat dalam mendeskripsikan pola kurva sorpsi isotermi beras pratanak, dan memprediksikan umur simpan beras pratanak dengan metode kadar air kritis. Sorpsi isotermi beras pratanak ditentukan dengan menggunakan metode gravimetri statis pada suhu 30o, dengan menggunakan larutan garam jenuh untuk mengatur kelembapan relatif. Untuk mencapai lingkungan kelembaban relatif yang berbeda, larutan NaOH, MgCl2, Mg(NO3)2, KI, NaCl, KCl, Na2SO4, dan NH4H2PO4 dengan kelembaban relatif berturut turut7%,33%,52%,69%,75%,84%, 87%dan92%.Limagramsampel beraspratanakdisimpandalam desikator. Sampel ditimbang secara berkala hingga mencapai berat konstan.Model Hasley, Oswin, Henderson, Chen-Clayton dan Caurie diterapkan untuk menggambarkan hubungan antara kadar air kesetimbangan dan kelembaban relatif. Mean Relative Determination digunakan untuk mengevaluasi ketepatan masing-masing model. Hasil penelitian menunjukkan bahwa kadar air kesetimbangan beras pratanak pada RH 7%, 33%, 52%, 69%, 75%, 84%, 87% dan 92% berturut-turut adalah 6.93% bk, 11.09% bk, 14.22% bk, 15.86%bk, 17.05% bk, 19.68% bk, 23.92% bk, dan 25.59% bk. Kurva sorpsi isotermi beras pratanak memiliki bentuk sigmoid. Model Oswinadalah model yang paling tepat dalam menggambarkan sorpsi isotermi beras pratanak dengan nilai MRD sebesar 3.85 dan R2sebesar 0.98. Beras pratanak yang dikemas dengan HDPE, LDPE, dan PP memiliki umur simpan berturut 2.2 tahun, 2.3 tahun dan 8.8 tahun.